Relevance of N-acetyltransferase 1 and 2 (NAT1, NAT2) genetic polymorphisms in non-small cell lung cancer susceptibility - Wikman, Harriet; Schmezer, Peter; Spiegelhalder, Bertold; Edler, Lutz; Dienemann, Hendrik; Kayser, Klaus; Schulz, Volker; Drings, Peter; Bartsch, Helmut; Risch, Angela (Pharmacogenetics and genomics, 2001)
The highly polymorphic N-acetyltransferases (NAT1 and NAT2) are involved in both activation and inactivation reactions of numerous carcinogens, such as tobacco derived aromatic amines. The potential effect of the NAT genotypes in individual susceptibility to lung cancer was examined in a hospital based case-control study consisting of 392 Caucasian lung cancer patients [152 adenocarcinomas, 173 squamous cell carcinomas (SCC) and 67 other primary lung tumours] and 351 controls. In addition to the wild-type allele NAT1*4, seven variant NAT1 alleles (NAT1*3, *10, *11, *14, *15, *17 and *22) were analysed. A new method based on the LightCycler (Roche Diagnostics Inc.) technology was applied for the detection of the polymorphic NAT1 sites at nt 1088 and nt 1095. The NAT2 polymorphic sites at nt 481, 590, 803 and 857 were detected by polymerase chain reaction-restriction fragment length polymorphism or LightCycler. Multivariate logistic regression analyses were performed taking into account levels of smoking, age, gender and occupational exposure. An increased risk for adenocarcinoma among the NAT1 putative fast acetylators [odds ratio (OR) 1.92 (1.16-3.16)] was found but could not be detected for SCC or the total case group. NAT2 genotypes alone appeared not to modify individual lung cancer risk, however, individuals with combined NAT1 fast and NAT2 slow genotype had significantly elevated adenocarcinoma risk [OR 2.22 (1.03-4.81)] compared to persons with other genotype combinations. These data clearly show the importance of separating different histological lung tumour subtypes in studies on genetic susceptibility factors and implicate the NAT1*10 allele as a risk factor for adenocarcinoma.
Gesehen am 28.01.2021